The personal fonds of Dandar-ool Kok-Khunaevich Oorzhak in the National Archives of the Republic of Tuva - Kharunov, Ramil Sh.; Kharunova, Marianna M.-B.; Oyun, Dolaana D. (The New Research of Tuva, 2022)
The article presents an analysis of the fonds of personal documents related to Dandar-ool Kok-Khunaevich Oorzhak (born in 1937), an outstanding political and public figure of Tuva in the Soviet period. It is stored in the National Archives of the Republic of Tuva. As part of the fonds, 196 units have been systematized and grouped into four sections: “Personal documents”, “Creative documents”, “Documents on official activities”, “Documents collected by the creator of the fonds”.The personal documents consist of autobiographies, characteristics and educational records, creative documents, i.e. published books and drafts of works. The most extensive section includes documents concerning official activities. It reflects the longstanding work of D. K.-Kh. Oorzhak in Komsomol and party bodies of the Tuvan ASSR. Numerous texts of speeches, entries in work logs allow a researcher to deal with the atmosphere of Soviet construction. The section “Documents collected by the creator of the fonds” comprises photographs that help to visualize the age. One can see people, meetings with collectives, various objects on the territory of the Republic.
Keywords: Dandar-ool Kok-Khunaevich Oorzhak; personal fonds; documents of personal origin; Tuva; history of Tuva